Sentiment Analysis of Madura Tourism Opinion Using Support Vector Machine (SVM) - Doni Abdul Fatah; Eka Mala Sari Rochman; Fajrul Ihsan Kamil; Ahmad Su’ud (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Madura is one of the most popular tourist destinations in Indonesia. It offers a variety of interesting attractions such as beaches, islands and a unique traditional culture. However, like other tourist destinations, Madura tourism also receives different opinions from the community. Some public opinions can be in the form of positive, negative and neutral feelings towards Madura tourism. To find out the public opinion, it is necessary to conduct sentiment analysis using the Support Vector Machine (SVM) method. In this analysis, data was collected from various social media platforms discussing Madura tourism. Reviews from the community are divided into three categories into positive, negative, neutral, which are processed by the SVM method. The purpose of using the Support Vector Machine method for sentiment analysis of public opinion about Madura tourism where the results can be analysed to provide recommendations for improvements to Madura tourism that are useful for improving the quality of Madura tourism based on public sentiment. From the test results carried out using K = 5 fold cross validation, positive sentiment is obtained from as many as 192 tweets and an accuracy of 92.592% using Confusion Matrix.